The 1970 Warsaw Treaty and the Challenges of Interpretative Declarations in International Treaty Law (Polish Yearbook of International Law, 2023)
The 1970 Warsaw Treaty lists a number of unilateral declarations, primarily on the part of the Federal Republic of Germany. Nowadays, in view of the fundamentally changed circumstances between Germany and Poland, these declarations no longer play a signifcant role. Nevertheless, it is interesting to dogmatically examine them, not only for legal historical reasons but also based on the acknowledged principle that the understanding of the present is always shaped by the past. This contribution aims to meet this challenge.